Pregnancy and childbirth after transvaginal natural orifice transluminal endoscopic surgery for benign gynecological diseases. Issue 3 (31st July 2021) - Feng, Dan; He, Li
Synopsis: Incision of the posterior vaginal fornix during vNOTES did not cause any negative effects on cervical dilation and vaginal extension in nine patients.